A Model of Increasing Quality of Life Among Rural Aging in Sukhothai Province - ศิริวนารังสรรค์, สมจิตต์; แสงเงิน, เสน่ห์ (Journal of Preventive Medicine Association of Thailand, 2018)
The objective of this study was to develop and examine the effectiveness of a model for developing quality of life among elderly in rural area. The study was conducted in 3 phases. The first phase aimed to assess factors associate with quality of life among elderly in rural area. The samples were 420 participants recruited by multistage random sampling. A questionnaire was administered by face to face interviews during December 2015 to March 2016; and analysis by Pearson’s product moment correlation coefficient. The result showed that such variables as age, income, knowledge, participation family activity, caring from family, health care system, basic human needed, environmental were associated with quality of life among elderly in rural area statistical significance. The second phase was to construct a model of develop quality of life among elderly in rural which consisted of the study on needs and quality of life suggested by stakeholders through five focus group discussions; and the content validity which was approved by five experts. The resulting model of develop quality of life among elderly consisted of 4 steps: (1) the learning aging and impact from aging; (2) learning skill participation family activity; and (3) the activities to self care behavior (4) the activities to environment conducive for life. The third phase was to evaluate effectiveness of a model for developing quality of life among elderly; and it was found that there was a significant increase in the average score of quality of life after the intervention (p<0.001). Therefore, this quality of life model should be applied and implemented for the elderly in rural areas.